Teacher Competence in Implementing Prezi-Assisted PowerPoint Media: A Case Study in Rural Elementary Education - Fia Regina Lestari; Rizal Rizal; Asriani Asriani; Herlina Herlina; Muhammad Nazimuddin AL Kamil; Surahman Wilade (Papanda Publisher, 2026)
This study examined teachers' abilities to implement Prezi-assisted PowerPoint media in elementary classroom instruction within a rural school context. Despite technological availability, effective integration of interactive multimedia remains challenging, particularly in resource-limited settings where infrastructural and capacity constraints impede implementation. A qualitative descriptive case study was conducted at SD Inpres 1 Kaluku Tinggu, Central Sulawesi, Indonesia, involving a Grade V teacher selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and documentation analysis, then analyzed using Miles and Huberman's framework involving data reduction, display, and verification. Findings revealed that the teacher demonstrated strong competence in instructional planning, classroom implementation, and formative assessment. Prezi-assisted PowerPoint significantly enhanced student engagement, with documented increases in student-initiated questions (47 versus 12 in conventional lessons) and participation rates. The teacher exhibited self-directed professional development, pedagogical reasoning, and adaptive strategies to overcome infrastructural challenges including limited internet connectivity and time constraints. The study confirms that effective technology integration depends primarily on teacher readiness and pedagogical skills rather than solely on infrastructural availability. Theoretically, findings extend multimedia learning and constructivist theories to authentic elementary contexts with resource constraints. Practically, results underscore the necessity for continuous professional development emphasizing pedagogical technology integration and institutional support systems addressing both technical and attitudinal barriers to sustainable innovation.